THE EFFECT OF “CLASH of KING” ONLINE MOBILE GAME ON TEACHING ENGLISH VOCABULARY - Abdullah Farih (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
AbstractLearning Vocabulary is an important and basic part of mastering language skill. The students are able to master language skills if he has good vocabulary. On the other hand, there is a big challenge for the English teacher in the remote area to make the students enthusiastic in learning English Vocabulary. Teacher needs to use something that is close to students’ life in teaching new vocabulary. Nowadays, mobile phone and games are something that cannot be separated from for students’ life. The teacher can use online mobile games like “Clash of Kings” as an alternative media to make students interested in learning English vocabulary. This research was conducted to know whether or not there is an influence of playing “Clash of King” online mobile game in teaching English vocabulary at the seventh grade of MTs. Al Fattah Banyuurip Ujungpangkah Gresik. The result of the research indicated that there is an influence of online mobile game “Clash of King” in teaching English vocabulary.